2023
DOI: 10.1021/acsami.2c18313
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of the Ferroelectric Properties in 100 nm-Thick Al0.72Sc0.28N

Abstract: The discovery of ferroelectricity in aluminum scandium nitride (Al1–x Sc x N) opens technological perspectives for harsh environments and space-related memory applications, considering the high-temperature stability of piezoelectricity in aluminum nitride. The ferroelectric and material properties of 100 nm-thick Al0.72Sc0.28N are studied up to 873 K, combining both electrical and in situ X-ray diffraction measurements as well as transmission electron microscopy and energy-dispersive X-ray spectroscopy. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…Guido et al also reported the wake-up phenomenon of AlScN when the measurement was performed at a high temperature (600 °C). 13 However, the wake-up phenomenon disappeared when the film was cooled down. Therefore, additional research is required to understand why AlScN exhibits wake-up characteristics at room temperature after 900 °C NH 3 annealing.…”
Section: Nh 3 Annealing Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Guido et al also reported the wake-up phenomenon of AlScN when the measurement was performed at a high temperature (600 °C). 13 However, the wake-up phenomenon disappeared when the film was cooled down. Therefore, additional research is required to understand why AlScN exhibits wake-up characteristics at room temperature after 900 °C NH 3 annealing.…”
Section: Nh 3 Annealing Effectmentioning
confidence: 99%
“…12 The FE properties of AlScN have demonstrated remarkable stability with thermal treatment, even above 1000 °C. 13,14 In addition, AlScN has the advantage of exhibiting ferroelectricity in its stable wurtzite structure, eliminating the need for additional heat treatment and other complicated steps to induce a FE phase. 9 In contrast, HfO 2 -based films require complex thermal treatment to exhibit ferroelectricity, leading to a high degree of variability in material parameters across different grains due to inhomogeneous film stress and multiple phases.…”
Section: Introductionmentioning
confidence: 99%
“…1,6,7 Thin-film w-Al x Sc 1−x N may also be integrated into GaNbased high-electron-mobility transistors and high-frequency power electronics. 8 The high temperature stability of the solid solution 9,10 and the ferroelectric Curie temperature crossing 1000 °C11 can be appealing for microwave and harshenvironment electronics. 12 However, ferroelectricity in Al x Sc 1−x N is not without limitations.…”
Section: Introductionmentioning
confidence: 99%
“…3 In this context, aluminum scandium nitride (Al 1−x Sc x N) with its large P r (>80 μC/cm 2 ) is a promising material for future applications, even in harsh environments due to its excellent thermal stability. 4,5 As a result of the high coercive fields (E c ) in Al 1−x Sc x N, very thin films are required to switch the ferroelectric layer between the two stable states (nitrogen (N)-polar and metal (M)-polar) at reasonable voltages for low-power memory applications. 4,6 Recent reports demonstrate that ferroelectric switching is achievable in 5 nm thick films with voltages below 6 V. 7−9 However, because E c is close to the breakdown field (E BD ) of the material, the cycling endurance still remains a critical reliability concern to address.…”
mentioning
confidence: 99%
“…The ferroelectric random-access memory (FeRAM) concept is frequently implemented in a single transistor–single capacitor (1T1C) cell, similar to a dynamic random-access memory cell except that the dielectric in the storage capacitor is replaced by a ferroelectric. , In a FeRAM array, the voltage difference sensed by a sense amplifier between the two memory states is directly proportional to the remanent polarization ( P r ) and the area of the ferroelectric capacitor; hence, ferroelectrics with large P r can increase the memory array density . In this context, aluminum scandium nitride (Al 1– x Sc x N) with its large P r (>80 μC/cm 2 ) is a promising material for future applications, even in harsh environments due to its excellent thermal stability. , As a result of the high coercive fields ( E c ) in Al 1– x Sc x N, very thin films are required to switch the ferroelectric layer between the two stable states (nitrogen (N)-polar and metal (M)-polar) at reasonable voltages for low-power memory applications. , Recent reports demonstrate that ferroelectric switching is achievable in 5 nm thick films with voltages below 6 V. However, because E c is close to the breakdown field ( E BD ) of the material, the cycling endurance still remains a critical reliability concern to address . The reported cycling endurance for Al 1– x Sc x N capacitors is far below the 10 13 cycles achievable in doped hafnia and lead zirconate titanate (PZT). The two major reliability aspects that determine capacitor endurance are the fatigue effect, which describes the reduction in P r with electric field cycling, and breakdown of the ferroelectric film.…”
mentioning
confidence: 99%